Protest and resistance in the tourist city. - (:unkn) unknown (Routledge, 2018)
Across the globe, from established tourist destinations such as Venice or Prague to less traditional destinations in both the global North and South, there is mounting evidence that points to an increasing politicization of the topic of urban tourism. In some cities, residents and other stakeholders take issue with the growth of tourism as such, as well as the negative impacts it has on their cities; while in others, particular forms and effects of tourism are contested or deplored. In numerous settings, contestations revolve less around tourism itself than around broader processes, policies and forces of urban change perceived to threaten the right to 'stay put', the quality of life or identity of existing urban populations. This book for the first time looks at urban tourism as a source of contention and dispute and analyses what type of conflicts and contestations have emerged around urban tourism in 16 cities across Europe, North America, South America and Asia. It explores the various ways in which community groups, residents and other actors have responded to - and challenged - tourism development in an international and multi-disciplinary perspective. The title links the largely discrete yet interconnected disciplines of 'urban studies' and 'tourism studies' and draws on approaches and debates from urban sociology, urban policy and politics, urban geography, urban anthropology, cultural studies, urban design and planning, tourism studies and tourism management.
Keywords: Stadtforschung; Stadtgeographie; Fremdenverkehr; Freizeitverkehr; Wohnen; Nutzungskonflikt; Bewohner; Gastgewerbe; Vermietung; Wohnung; Lärmbelastung; Städtetourismus; Ferienwohnung; Übernachtung; Widerstand; Protest; Massentourismus; Wirtschaftsfaktor; Städtevergleich; Internationaler Vergleich